Ustekinumab Exposure-outcome Analysis in Crohn's Disease Only in Part Explains Limited Endoscopic Remission Rates. (8th February 2019) - Verstockt, Bram; Dreesen, Erwin; Noman, Maja; Outtier, An; Van den Berghe, Nathalie; Aerden, Isolde; Compernolle, Griet; Van Assche, Gert; Gils, Ann; Vermeire, Séverine; Ferrante, Marc
Abstract: Background and Aims: Ustekinumab, an anti-IL12/23p40 monoclonal antibody, has been approved for Crohn's disease [CD]. Real-life data in CD patients receiving ustekinumab intravenously [IV] during induction, followed by subcutaneous [SC] maintenance, are lacking. We assessed efficacy of ustekinumab and studied exposure-response correlations. Methods: We performed a prospective study in 86 CD patients predominantly refractory or intolerant to anti-tumour necrosis factor agents and/or vedolizumab. All received ustekinumab 6 mg/kg IV induction, with 90 mg SC every 8 weeks thereafter. Endoscopic response (50% decrease in Simple Endoscopic Score for CD [SES-CD] at Week 24), endoscopic remission [SES-CD ≤2], and clinical remission [daily stool frequency ≤2.8 and abdominal pain score ≤1] were assessed at weeks 4, 8, 16, and 24. Further serial analyses included patient-reported outcomes [PRO2], faecal calprotectin [fCal], and ustekinumab serum levels. Results: SES-CD decreased from 11.5 [8.0–18.0] at baseline to 9.0 [6.0–16.0] at week [w]24 [ p = 0.0009], but proportions of patients achieving endoscopic response [20.5%] or endoscopic remission [7.1%] were low. Clinical remission rates were 39.5% at w24. After IV induction, fCal dropped from baseline [1242.9 μg/g] to w4 [529.0 μg/g] and w8 [372.2 μg/g], but increased again by w16 [537.4 μg/g] and w24 [749.0 μg/g]. A clear exposure-response relationship was observed, both during induction and during maintenance therapy, with different thresholds depending on the targeted outcome. Conclusions: In this cohort of refractory CD patients, ustekinumab showed good clinical remission rates but limited endoscopic remission after 24 weeks. Our data suggest that higher doses may be required to achieve better endoscopic outcomes.